Pengaruh Disiplin Kerja terhadap Peningkatan Kinerja Satuan Polisi Pamong Praja Kecamatan Panyabungan Kabupaten Mandailing Natal - Juliana Agustin Siregar; Vebri Sugiharto; Andy Hakim (Yayasan Literasi Sains Indonesia, 2025)
Disciplinary issues such as tardiness, unauthorized absences, and low compliance with regulations form the background of this study because they have an impact on the declining performance and image of the Civil Service Police Unit (Satpol PP) of Panyabungan District. This quantitative study was conducted at the Satpol PP of Mandailing Natal District from November 2024 to mid-2025 with a population of 229 employees and a sample of 70 respondents selected through simple random sampling. Data were collected through a 5-point Likert questionnaire and documentation, tested for validity and reliability (α Discipline = 0.884; α Performance = 0.767), and analyzed using SPSS version 20 with simple linear regression. The results show a positive and significant effect of work discipline on performance (B = 0.592; t = 12.482; p = 0.000), and a coefficient of determination R² = 0.696, which means that approximately 69.6% of the variation in performance can be explained by work discipline. These findings indicate that strengthening the disciplinary system, managerial supervision, and the implementation of consistent attendance and reward–sanction mechanisms should be prioritized as strategies to improve the productivity and credibility of the Satpol PP in Panyabungan.